MANAJEMEN PENDIDIKAN ISLAM: MANAJEMEN ORANG TUA TERHADAP ANAK - Bahrun Ali Murtopo (Yinyang: Jurnal Studi Islam Gender dan Anak, 2017)
All parents certainly expect their children to be pious people. However, unintentionally, they often treat them in the way that contradict with their expectation. So many people are busy doing their job. Reserches proves that children grown up without both parents’ supervision tend to have more problems than those grown up in under both parents’supervision (Dr Fakhir Aqil, ‘Ilm Al-Nafs Al-Tarbawi: 111). For that reson, in building a family, it is necessary to prepare an integrated and guided education program. This kind of program should be able to provide a clear job description for each individual in the family that enables each individual to play his/her roles to reach a condusive family environment for bringingup children optimally.